ERROR ANALYSIS ON THE AUXILIARY VERBS MADE BY THE TENTH GRADERS OF MAN 2 SAMARINDA - Siti Djulaikah (LINGUA : Jurnal Bahasa, Sastra, dan Pengajarannya, 2016)
This study used qualitative design focusing on the errors made by the second year students of MAN 2 Samarinda. The variable of this study was errors on auxiliary verbs. The variable was measured by using an objective test on auxiliary verbs. The instrument of the study was a test on auxiliary verbs. The data were analyzed the kinds of typical errors which are classified into four, they are: omission, addition, misformation, misordering errors. The components of auxiliary verbs test were: to do (do, does, did), to have (have, has), and modal auxiliary (can, could, will, would, may, and must).  The study discovered that kinds of typical errors on auxiliary verbs are classified into four kinds of typical errors: omission errors, addition errors (double marking and regularization), misformation errors and miscellaneous errors.  The typical errors present on auxiliary verbs are classified into four kinds of typical errors: (1) to do, including: errors in adding “do”, “does” and “did”, misuse in using “do”, “does” and “did”. (2) to have including: errors in adding “have” and “has”, double in marking auxiliary verbs, in this case to be and to have, (3) modal auxiliary including: false in choosing the right modal auxiliary.